PENGARUH MODEL PEMBELAJARAN BAMBOO DANCING TERHADAP KREATIVITAS SISWA - Sarumaha, Murnihati (Unversitas Katolik Santo Thomas, 2021)
This study aims to determine the effect of the Bamboo Dancing learning model on students' creativity in Biology subjects. The research method used was a quasi-experimental research design with a pretest and posttest group design. The study population was all students of class X-MIA, while the research sample was students of class X-MIA-a as the experimental class and class X-MIA-b as the control class. The results showed that the average percentage the initial creativity the experimental class students was 59.7% and the control class students 56.4%. Through the Bamboo Dancing learning model, the average percentage the final creativity the experimental class students was 83.8%, while through the conventional learning model the average percentage the final creativity control class students was 68.9%. Hypothesis testing obtained tcount = 10.292 while ttable at a significant level of 5% and dk = 17-2 = 15 with ttable = 2.132, it turns out that tcount> ttable or 10.292> 2.132 so that Ha is accepted. Experimental class students are able express ideas and be able to think creatively to solve problems. So it can be concluded that there is an effect of the Bamboo Dancing learning model on students' creativity where students able to think creatively to solve problems.